2015
DOI: 10.1016/j.coviro.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species transmission and emergence of novel viruses from birds

Abstract: Birds, the only living member of the Dinosauria clade, are flying warm-blooded vertebrates displaying high species biodiversity, roosting and migratory behavior, and a unique adaptive immune system. Birds provide the natural reservoir for numerous viral species and therefore gene source for evolution, emergence and dissemination of novel viruses. The intrusions of human into natural habitats of wild birds, the domestication of wild birds as pets or racing birds, and the increasing poultry consumption by human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 71 publications
1
63
0
3
Order By: Relevance
“…In addition to the sylvatic (enzootic) transmission cycle between the haematophagous mosquito vectors and susceptible primary vertebrate hosts, the recent large-scale epidemics suggest that ZIKV is also adapting to an urban transmission cycle. 52,53 Among the various mosquito species, Aedes (Stegomyia) mosquitoes appear to be the most important vector for ZIKV transmission, although some Anopheles, Culex, Eretmapodites, and Mansonia species have also been proposed as possible vectors (Table 2). 25,52,54e69 The animal reservoirs of ZIKV are unclear.…”
Section: Routes Of Transmissionmentioning
confidence: 99%
“…In addition to the sylvatic (enzootic) transmission cycle between the haematophagous mosquito vectors and susceptible primary vertebrate hosts, the recent large-scale epidemics suggest that ZIKV is also adapting to an urban transmission cycle. 52,53 Among the various mosquito species, Aedes (Stegomyia) mosquitoes appear to be the most important vector for ZIKV transmission, although some Anopheles, Culex, Eretmapodites, and Mansonia species have also been proposed as possible vectors (Table 2). 25,52,54e69 The animal reservoirs of ZIKV are unclear.…”
Section: Routes Of Transmissionmentioning
confidence: 99%
“…F requent mixing of different animal species in markets in densely populated areas and human intrusions into the natural habitats of animals have facilitated the emergence of novel viruses. Examples with specific geographical origins include severe acute respiratory syndrome coronavirus (SARS-CoV) and avian influenza A/H7N9 and H5N1 viruses in China, Nipah virus in Malaysia and Bangladesh, and Ebola and Marburg viruses in Africa (1)(2)(3)(4)(5)(6)(7)(8)329). The Middle East is a region encompassing most of western Asia and Egypt and contains 18 countries with various ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…A cute respiratory tract infections are associated with significant morbidity and mortality in hospitalized patients (1)(2)(3). In addition to the "classical" viral or bacterial respiratory pathogens such as seasonal influenza A viruses and Streptococcus pneumoniae, numerous infectious agents, including the human metapneumoviruses (hMPV), bocavirus (HBoV), human coronaviruses (HCoV), and avian influenza A/H7N9 virus, have been identified to cause severe human infections in recent years (4)(5)(6)(7)(8)(9)(10). Mixed infections with two or more respiratory pathogens are common in children, and studies have shown an increased risk of more-severe community-acquired pneumonia in these patients (11,12).…”
mentioning
confidence: 99%